2021
DOI: 10.3390/ijerph182312800
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Awareness and Actual Nursing Practice Situation of Stroke Care in Acute Stroke Units: A Japanese Cross-Sectional Web-Based Questionnaire Survey

Abstract: The awareness of care provided by stroke care unit (SCU) nurses in Japan to patients with an acute cerebrovascular accident (CVA) and the characteristic differences in their actual nursing practice were evaluated. A cross-sectional web-based questionnaire survey was administered to 1040 SCU nurses. Data collection and reporting procedures followed the STROBE Statement Checklist for cross-sectional studies. Exploratory factor analysis, using 52 observation items, identified eight factors with a factor loading &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
2
11
0
3
Order By: Relevance
“…According to subjects' educational qualification, the higher percent (41.67%) of the respondents was holding technical institute in nursing. This agreement with Hisaka et al, (2021), andIslam (2018) who found that most 80 of nurses had nursing diplomas, and result pointed that technical institute, nurses number are more than any other educational qualification. (Mohammed, et al, 2021) found that the half of study sample (50%) were holding technical institute in nursing.…”
Section: Discussionsupporting
confidence: 85%
“…According to subjects' educational qualification, the higher percent (41.67%) of the respondents was holding technical institute in nursing. This agreement with Hisaka et al, (2021), andIslam (2018) who found that most 80 of nurses had nursing diplomas, and result pointed that technical institute, nurses number are more than any other educational qualification. (Mohammed, et al, 2021) found that the half of study sample (50%) were holding technical institute in nursing.…”
Section: Discussionsupporting
confidence: 85%
“…were bedside nurses, from the researcher point of view this result may be due to job description distribution in the hospital as bedside nurses responsible for providing care to patients in all hospital departments. This result goes in the same line with (Hisaka et al, 2021) their study about nurses' awareness and actual nursing practice situation of stroke care in acute stroke units: a Japanese crosssectional web-based questionnaire survey, who found that majority of all participants (90.5%) were staff nurses.…”
Section: Discussionsupporting
confidence: 78%
“…( Knowledge about care of stroke patients (25) closed ended questions which included; assist patients with medications, feeding, self-care, activities of daily living, caring for skin, changing position, mobilization, follow up, maintaining safety, coping with life stressors and provide emotional support.…”
Section: Tools For Data Collectionmentioning
confidence: 99%
“…Our study supports this evidence as only 25% of the nurses are trained and 32% are experienced in acute poisoning management. In one study conducted in Japan, a great difference was found between actual practice and awareness among stroke care unit nurses [ 15 ]. In an online survey reported in Singapore, it was found that nurses with higher education or experience in an emergency got more knowledge scores [ 16 ].…”
Section: Discussionmentioning
confidence: 99%